Bjerkandera carnegieae comb. nov. (Phanerochaetaceae, Polyporales), a wood-decay polypore of cactus - Robledo, Gerardo Lucio (2021)
Poria carnegieae was described from Arizona growing on the woody ribs of the saguaro cactus, Carnegiea gigantea, and was transferred to Ceriporiopsis due to morphological evidence. Posterior phylogenetic studies showed a relationship of Poria carnegieae with Bjerkandera. New sequence data and morphologic evidence are presented to support the transfer of Ceriporiopsis carnegieae to Bjerkandera.